Du Oaxaca à la ville de Mexico : l’accès aux ressources urbaines - Antonine Ribardière (EchoGéo)
This paper aims at studying the process of insertion of migrants from rural origin in Mexico City. The analysis is built around the concept of urban resources. In this way, we want to highlight how site’s resources, individual resources and social and familial network’s resources are all linked together. This analysis is based on one hand on detailed data of the Mexican’s census that allow us to identify the working and housing statuses of the migrants from Oaxaca, and on the other hand on an empirical survey carried out in the industrial district of Naucalapan. It emphasizes the importance of sub-central areas in the reception of migrants and in their access to the urban resources.